THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND PROMOTION ON CONSUMER SATISFACTION WITH SMARTPHONES - Dewi Andriany; Mutia Arda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Abstract*